Mine Blasting Accident Update - John W. Kopp; Larry R. Fletcher (International Society of Explosives Engineers, 1991)
The safety record for explosives in U. S. mining is excellent considering that over 4 billion pounds of explosives are now being used each year. However, blasting accidents remain one of the most serious concerns based on the number of injuries, the injury severity rate and the disaster potential. The Bureau of Mines has been analyzing blasting accident data obtained from the Mine Health and Safety Administration (MSHA) to determine the most frequent causes of mine blasting accidents and to examine trends in blasting accidents. This accident analysis is an update of two previous blasting accident studies conducted by the Bureau and published in 1983 and 1987.